Distinguishing the impacts of climate change and anthropogenic factors on vegetation dynamics in the Yangtze River Basin, China. (January 2020) - Qu, Sai; Wang, Lunche; Lin, Aiwen; Yu, Deqing; Yuan, Moxi; Li, Chang'an
Graphical abstract: Contributions of climate factors and anthropogenic activities to EVI trend in the YRB. Highlights: An increasing trend of vegetation coverage in YRB was observed. Temperature made the greatest contribution to EVI inter-annual trend. Human activities were the main factors leading to vegetation restoration. Urbanization has caused vegetation degradation in urban agglomerations. Abstract: Assessing and attributing vegetation dynamics can provide essential information for environmental resources management, particularly for those regions with fragile ecosystems. The Yangtze River Basin (YRB), a region of pivotal importance to the ecological balance and security of China, has experienced dramatic changes in environment and landscape driven by climate change and human activities, especially afforestation projects in recent years. Yet how the driving factors contribute quantitatively to vegetation dynamics is not well established. Here we investigate spatiotemporal variability of vegetation coverage in terms of the Enhanced Vegetation Index (EVI) over 2001–2015, and analyze the actual influences of various climatic factors on EVI inter-annual variations. Further analysis quantifies the contributions of climate change and anthropogenic factors to EVI inter-annual variations. The results show that over the 15-year period, the average EVI demonstrated fluctuations but denoted a generally upward trend, with an increasing rate of 0.0027/a. According to the Hurst exponent analysis, areas with consistent improvement were primarily concentrated in Hunan Province and eastern Sichuan Province, where the main vegetation types are broadleaf forest and mixed forest. The average contributions of temperature, precipitation and solar radiation to EVI inter-annual variations in the YRB was 0.0041/a, 0.00012/a, and −0.0034/a, respectively. Temperature was the controlling climate factor, with the greatest contribution to EVI inter-annual variations, while solar radiation made strong negative contributions. The average contributions of climate change and anthropogenic factors to EVI inter-annual variations were 0.0008/a and 0.0019/a, accounting for 70.37% and 29.63% of the total EVI changes respectively. Human activities, especially ecological afforestation projects, were the main driving factors improving vegetation coverage in the YRB, and the spatial distribution of forest gains was consistent with the positive contribution of human activities to the EVI trend. However, urbanization has occupied the growth space of vegetation and was a negative human-induced factor affecting vegetation growth.